Jornalismo guiado por Dados em Quadrinhos: Arte sequencial desmistificando a tecnologia - BARROS, Virginia Cunha (2022)
This multidisciplinary work presents the development process of our product, which consists of a comic book aimed at professionals and undergraduate students of Social Communication and Journalism. The objective of the product is to introduce the main concepts of Data-Driven Journalism, creating an informative booklet on the subject that is capable of presenting the contents in a clear and pleasant way to an audience with no previous knowledge in the area. A bibliographic review was presented regarding the changes caused in the last century in the field of Journalism, with the increasing presence of computers and similar computer accessories in the environment of journalistic newsrooms. Thus, there is a growing need for specific knowledge to use these technological tools, culminating in the emergence of the multidisciplinary journalistic area known as Data-Driven Journalism (DDJ), in which traditional journalism benefits from technological resources, which are modern and in constant updating. A partnership was developed with Prof. Dr. Benedito Medeiros Neto (in memorian) and his respective students of the Data Journalism discipline of the Computer Science course at the University of Brasília, with the objective of deepening the knowledge in the practice of the mentioned area and its possible intersections with Communication and the Journalism. We also prepared a theoretical review on the history of sequential art, also known as the art of Comics, with the aim of building methodological knowledge for the elaboration of our Comics. We revisited the Comics landmarks, theoretical and practical references in the area, its symbology, language and verbal and non-verbal communication. We point out that the field of comics already presents an intersection with Journalism, through Journalism in Comics found in references such as Joe Sacco and Art Spiegelman. We present the prototype of the product that resulted from our research and from the practical application of the theoretical foundation found.